Prehospital Triage of Acute Ischemic Stroke Patients to an Intravenous tPA-Ready versus Endovascular-Ready Hospital: A Decision Analysis. (2nd November 2018) - Benoit, Justin L.; Khatri, Pooja; Adeoye, Opeolu M.; Broderick, Joseph P.; McMullan, Jason T.; Scheitz, Jan F.; Vagal, Achala S.; Eckman, Mark H.
Abstract: Background : American Stroke Association guidelines for prehospital acute ischemic stroke recommend against bypassing an intravenous tPA-ready hospital (IRH), if additional transportation time to an endovascular-ready hospital (ERH) exceeds 15–20 min. However, it is unknown when the benefit of potential endovascular therapy at an ERH outweighs the harm from delaying intravenous therapy at a closer IRH, especially since large vessel occlusion (LVO) status is initially unknown. We hypothesized that current time recommendations for IRH bypass are too short to achieve optimal outcomes for certain patient populations.Methods : A decision analysis model was constructed using population-based databases, a detailed literature review, and interventional trial data containing time-dependent modified Rankin Scale distributions. The base case was triaged by Emergency Medical Services (EMS) 110 min after stroke onset and had a 23.6% LVO rate. Base case triage choices were (1) transport to the closest IRH (12 min), (2) transport to the ERH (60 min) bypassing the IRH, or (3) apply the Cincinnati Stroke Triage Assessment Tool and transport to the ERH if positive for LVO. Outcomes were assessed using quality-adjusted life years (QALYs). Sensitivity analyses were performed for all major variables, and alternative prehospital stroke scales were assessed.Results : In the base case, transport to the IRH was the optimal choice with an expected outcome of 8.47 QALYs. Sensitivity analyses demonstrated that transport to the ERH was superior until bypass time exceeded 44 additional minutes, or when the onset to EMS triage interval exceeded 99 min. As the probability of LVO increased, ERH transport was optimal at longer onset to EMS triage intervals. The optimal triage strategy was highly dependent on specific interactions between the IRH transportation time, ERH transportation time, and onset to EMS triage interval.Conclusions : No single time difference between IRH and ERH transportation optimizes triage for all patients. Allowable IRH bypass time should be increased and acute ischemic stroke guidelines should incorporate the onset to EMS triage interval, IRH transportation time, and ERH transportation time.